A protocol for EBT3 radiochromic film dosimetry using reflection scanning. Issue 12 (14th November 2014) - Papaconstadopoulos, Pavlos; Hegyi, Gyorgy; Seuntjens, Jan; Devic, Slobodan
Abstract : Purpose: To evaluate the performance of the EBT3 radiochromic film dosimetry system using reflection measurements and to suggest a calibration protocol for precise and accurate reflection film dosimetry. Methods: A set of 14 Gafchromic EBT3 film pieces were irradiated to various doses ranging from 0 to 8 Gy and subsequently scanned using both the reflection and transmission mode. Scanning resolution varied from 50 to 508 dpi (0.5–0.05 mm/pixel). Both the red and green color channels of scanned images were used to relate the film response to the dose. A sensitivity, uncertainty, and accuracy analysis was performed for all scanning modes and color channels. The total uncertainty, along with the fitting and experimental uncertainty components, was identified and analyzed. A microscope resolution target was used to evaluate possible resolution losses under reflection scanning. The calibration range was optimized for reflection scanning in the low (<2 Gy) and high (>2 Gy) dose regions based on the reported results. Results: Reflection scanning using the red channel exhibited the highest sensitivity among all modes, being up to 150% higher than transmission mode in the red channel for the lowest dose level. Furthermore, there was no apparent loss in resolution between the two modes. However, higher uncertainties and reduced accuracy were observed for the red channel under reflection mode, especially at dose levels higher than 2 Gy. These uncertainties were mainly attributed to saturation effects which were translated in poor fitting results. By restricting the calibration to the 0–2 Gy dose range, the situation is reversed and the red reflection mode was superior to the transmission mode. For higher doses, the green channel in reflection mode presented comparable results to the red transmission. Conclusions: A two‐color reflection scanning protocol can be suggested for EBT3 radiochromic film dosimetry using the red channel for doses less than 2 Gy and the green channel for higher doses. The precision and accuracy are significantly improved in the low dose region following such a protocol.